PENDIDIKAN ISLAM DALAM PERSPEKTIF INTERNASIONAL WORLD MUSLIM COMPERENCE ON EDUCATION: Telaah Ontologis, Epistemologis dan Aksiologis - Siagian, Mhd. Darwis; Hanum Ok, Azizah (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2024)
The problems studied in the International seminar on Islamic Education are often important information. So that the author wants to study more specifically and know how to understand the concept of Islamic Education in the aspect of Islamic education conferences in ontological, epistemological, and axiological concepts. This research is a type of library research (literature study). For this reason, this research focuses on literacy work as a basis without the need for field research. The method used in this study is qualitative method. This world Islamic education seminar is not timed, this seminar can be formed at any time in accordance with the agreement, there is no difference between general knowledge and religion and the integration of science.